Теоретичні засади вивчення девіантної комунікації - Єльнікова, Н. І.; Yelnikova, N. I.; ORCID: http://orcid.org/0000-0002-5061-8226 (Вчені записки ТНУ імені В. І. Вернадського. Сер.: Філологія. Журналістика. – 2021. – Т. 32 (71), № 4, ч. 1. - С. 18-23, 2021)
Проаналізовано теоретичні основи і напрями тлумачення девіантної комунікації в сучасних наукових розвідках крізь призму різноманітних факторів демонстрації такого спілкування в суміжних із мовознавством наукових галузях.

The article attempts to investigate the theoretical foundations of deviant communication, to describe the current state of research on the problem of deviation, proposes the definition of deviation as a term, the views of scientists on the problems of its determination. Emphasis is placed on the study of works of domestic and foreign scientists in various fields. The need to focus on the creation and implementation of Internet text, distributed among the general public, for a stable and tolerant society is emphasized. Scientific research analyzes the works of domestic and foreign scientists on the problem of deviant communication as an interdisciplinary phenomenon. A range of problematic issues that require linguistic analysis to clarify the status characteristics of deviation in communication is identified. The opinion is substantiated that the term “deviation” does not have a single interpretation in different sciences, as it appeared relatively recently and is in the process of development today. The etymology of the concepts “deviance”, “deviation”, “deviant behavior”, “deviant communication” is given, the definition of the given concepts is formed. The components that characterize deviant human behavior are highlighted. The processes of external social conditions that affect human behavior are identified. The problems of deviation of modern researchers, which are mainly due to the mismatch between human needs and regulatory requirements, are outlined. The study analyzes the philosophical, legal, psychological, cultural, linguistic typified and inseparable vision of the problems of definition, theoretical justification and study of deviant communication as a deviation from the normative activities of different systems. It is proposed to study three core postulates during the study of deviant communication: normative – individual, deviant. The method of studying deviation in the systemtheoretical cognitive-communicative aspects is outlined and the opinions of scientists on the outlined problem within the limits of the modern linguistic paradigm are systematized.

Проанализированы теоретические основы и направления толкования девиантной коммуникации в современных научных исследованиях сквозь призму различных факторов демонстрации такого общения в смежных с языкознанием научных областях.
Theoretical fundamentals of the study of deviant communication
Єльнікова, Н. І. Теоретичні засади вивчення девіантної комунікації / Єльнікова Н. І. //Вчені записки ТНУ імені В. І. Вернадського. Сер.: Філологія. Журналістика. – 2021. – Т. 32 (71), № 4, ч. 1. - С. 18-23. - DOI: https://doi.org/10.32838/2710-4656/2021.4-1/04.
Keywords: Мова. Мовознавство. Літературознавство. Language. Linguistics. History and Criticism of Literature. Язык. Языкознание. Литературоведение; Наукові публікації. Scientific publications. Научные публикации; девіація; deviation; девиация; Інтернет; Internet; Интернет; девіантна комунікація; deviant communication; девиантная коммуникация; девіантна поведінка; deviant behavior; девиантное поведение; Інтернет-комунікації; Internet communications; Интернет-коммуникации; погляди вчених; views of scientists; взгляды ученых